Analisis Dampak Covid-19 terhadap Perilaku Konsumen Generasi Milenial dalam Menggunakan Aplikasi Dompet Digital - Iyus Wiadi; Mohamad Sajili (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This research discusses the impact of the Covid-19 pandemic on consumer behavior in using digital wallets as a digital payment method in transactions. The purpose of this study is to determine consumer behavior for quick and unplanned purchases (impulse purchases) depending on the product campaign and payment method used. The research method uses a qualitative descriptive method. The results of the study show that Covid-19 leads to an increase in shopping behavior when using digital wallets. In addition, changes have occurred due to the demands and needs of the digital era as well as changes in the new culture from traditional payments to electronic payments. The four factors, namely cultural, social, personal, and psychological factors influence changes in consumer behavior in using digital wallets for daily transactions.